Suitability of Microclimate for Maize and Edamame - Fatiha Zacky Nurikadevi; Mahindra Dewi Nur Aisyah; Iqbal Erdiansyah; Ilham Muhklisin; Tirto Wahyu Widodo (International Integrated Agricultural Journal (IIAJ), 2026)
Climate change impacts on maize cause a decrease in yields, changes in phenology, heat stress, water scarcity, and vulnerability to pests and diseases. Enhancing agricultural resilience to climate change highly recommended using intercropping between maize and edamame. This research aims to determine the suitability of climatic factors for maize and edamame in different patterns (monoculture of maize; intercropping of maize and edamame; intercropping with basil; and intercropping with lemongrass). This research was conducted from June to September 2024 in the Kebonsari field, Jember. The results show that climate factors affect maize and edamame soybean plants, particularly soil temperature and humidity, which have an influence of more than 50%.